Integration of coastal urban farming for agrotourism development in the Ampenan heritage area - Husnul Jannah; Habibi; Aida Muspiah; Siska Cicilia; Moegraturl Amaro (Journal of Biology, Environment, and Edu-Tourism, 2025)
As part of efforts to promote sustainable tourism aligned with local cultural values, this study was conducted to formulate a development model for Green Heritage Tourism by integrating coastal urban farming within the Ampenan Heritage Area of Mataram City. A descriptive–qualitative approach was employed, supported by spatial analysis, field observations, in-depth interviews, and focus group discussions. The findings indicate that the Ampenan heritage area possesses significant historical and cultural value but faces ecological challenges, including coastal abrasion, limited green space, and increasing urban pressure. The integration of coastal urban farming, including hydroponics, vertical farming, and saline-tolerant crops, is considered effective in enhancing environmental quality, expanding productive green spaces, and enriching educational tourism attractions. Community participation is a crucial factor in the implementation process. This study develops a model comprising three pillars: heritage preservation, productive coastal ecology, and local economic empowerment. As a recommendation, local government and stakeholders are encouraged to adopt this model as a reference for policy formulation and revitalization strategies to ensure that Ampenan grows into a more adaptive, sustainable, and competitive heritage-based tourism destination.